Resilient platoon control for autonomous connected vehicles under actuator faults and cyberattacks - Tan, Guo Li (Nanyang Technological University, 2021)
Abstract— This report is concerned with actuator fault and cyberattacks, the two most important factors in platoon connected vehicular system. The fault in actuator and attack signals are classified as unknown signals for our analysis. The purpose is to analyse the fault-tolerant control in-vehicle platoon that contains these unknown signals under fault occurrence. In the thesis of this report, we incorporated the fault-tolerant control design regarding the studies in [1][2]. Then, we develop a fault model to simulate and examine the effects of each parameter of the platoon CAVs system. This fault model will investigate the parameters that could cause instability and determine the parameters that can help us achieve better performance in the platoon CAVs. Also, we will deepen our understanding and knowledge of cyberattacks that could occur in the platoon vehicle system and affect the reliability of the overall vehicle platoon system. Finally, the simulation results obtained from MATLAB will help us to determine the robustness and effectiveness under the influence of each input parameter that will affect the stability of the CAVs under a different fault scenario.